Pendampingan Pelabelan Produk Pada UMKM Mbah Bendo Koi Kelurahan Bendo Kota Blitar - Santi Eka Rahmawati; Yanda Bara Kusuma (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Indonesia is a developing country which also has various challenges from various aspects, one of which is the economic field. The emergence of rapid technological developments also makes business actors such as MSMEs also have to be able to keep up with the current developments. By utilizing technology, marketing activities can be carried out on an online basis using the internet. The presence of the internet for life provides various kinds of impacts and changes. The changes that occur can be easily felt around us. Activities that were originally manual or conventionally are now carried out on an online basis with sophisticated and advanced technology that provides convenience in carrying out daily activities. In this developing digital era, its use is not only as a hBapakran or communication media.